Inflammation and Neovascularization in Hip Impingement: Not Just Wear and Tear. (August 2015) - Elias-Jones, Cameron J.; Farrow, Luke; Reilly, James H.; Kerr, Shauna; Meek, R. M. Dominic; Kelly, Michael P.; Campton, J. Luke; Millar, Neal L.
Background: Femoroacetabular impingement (FAI) is a significant cause of osteoarthritis (OA) in young active patients, but the pathophysiology remains unclear. Increasingly, mechanistic studies point toward an inflammatory component in OA. Purpose: This study aimed to characterize inflammatory cell subtypes and neovascularization in FAI by exploring the phenotype and quantification of inflammatory cells and neovascularization in FAI versus OA samples. Study Design: Descriptive laboratory study. Methods: Ten samples of the labrum were obtained from patients with FAI (confirmed diagnosis) during open osteochondroplasty or hip arthroscopic surgery. Control samples of the labrum were collected from 10 patients with OA who were undergoing total hip arthroplasty. Labral biopsy specimens were evaluated immunohistochemically by quantifying the presence of macrophages (CD68, CD206, interleukin-13 [IL-13]), T cells (CD3), mast cells (mast cell tryptase), and vascular endothelium (CD34, vascular endothelial growth factor). Results: Labral biopsy specimens obtained from patients with FAI exhibited significantly greater macrophage, mast cell, and vascular endothelium expression compared with control OA labral samples ( P < .05). The most significant difference was noted in macrophage ( P < .01) and mast cell ( P < .05) expression. Further subtyping of macrophages in FAI using the CD206 tissue marker and IL-13 revealed an M2 phenotype, suggesting that these cells are involved in a regenerate versus degenerate process. There was a modest but significant correlation between mast cells and CD34 expression ( r = 0.4, P < .01) in FAI samples. Conclusion: This study provides evidence for an inflammatory cell infiltrate in FAI along with significant neovascularization. In particular, the significant infiltration of mast cells and macrophages was demonstrated, suggesting a role for innate immune pathways in the events that mediate hip impingement. Clinical Relevance: Further mechanistic studies to evaluate the net contribution and hence therapeutic utility of these cellular lineages and their downstream processes may reveal novel therapeutic approaches to the management of early hip impingement.